IMPLEMENTASI AES UNTUK KEAMANAN APLIKASI FORMULIR ONLINE - Andri Firnandius; Lely Hiryanto (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
Google Forms software is an online application which users can create form for various purpose. The application can store information or data that has been provided by the form fillers. The form fillers are merely identified by their institutional email's domain or those with the access link to the make response for each question provided in an online form. The use of third-party applications certainly reduces the sense of trust in the security of the data provided. Therefore, a digital form application design was created with the Advanced Encryption Standard (AES). The aim is to maintain the security of the data provided by the form filler and ensure that the fillers are those with the authority.